The Role of the Access Environment in Metro Commute Travel Satisfaction - Zacharias, John; Liu, Xinyi (Sustainability, 2022)
The contributions of the access and egress portions of public transport trips to overall travel satisfaction merit more attention. This study collected responses from intercepted regular urban rail travelers at three metro stations with distinct built-form and land-use characteristics. Local conditions of access on foot, by bicycle, or on a bus were evaluated retrospectively on a five-point satisfaction scale and compared with an independent survey of the same access routes. Three-factor theory and dummy variable regression methods were used to identify the factor structure of environmental attributes under different access means. In the results, access and egress satisfaction were more important than metro trip satisfaction in overall trip satisfaction for walking and cycling modes. Access distance was not significant for walking and marginally negative for cycling satisfaction. For pedestrians, street connectivity, pathway directness, shade, greenery, and crossing safety were all significant (p < 0.05), explaining 51% of the variance in expressed satisfaction. For bicyclists, directness, distance, service, and parking facilities were significant in satisfaction, accounting for 62% of variance. In the bus access model, we found that bus stop location is very important, with passengers also very concerned about the walk experience to the bus stop. Satisfaction with access and egress environments is important in overall satisfaction with travel by public transport.